Knowledge and Psychological Factors Affecting on Skills Performance Enhancement and Developing Reading (Medico Legal Update, 2020)
The current research aims to building proposed standards to evaluate the performance of teachers of theArabic language male and female teachers in according to the quality systems of modern education andaccording to the following areas: ((Planning, learning strategies, scientific material, assessment, teacher’sprofession)),The number of standards (16) criteria and the number of indicators (72) and I developed foreach paragraph five alternatives (Excellence, very good, good, average, acceptable), and verified the validityof the tool and its stability, which has been applied by the researcher on a sample of teachers and teachersof the language in the center of the province numbered (193) male and female, the researcher found that theperformance of teachers both gender was generally positive which calls for more attention to the preparationand training of teachers according to quality performance standards.